The Influence of Human Resources Audit and Internal Control System on Employee Performance in PT. Subur Sedaya Maju Prabumulih - Mardiana, Tri; Praja, Rico Adrian; Pratiwi, Krisnandini Wahyu (AIBPM Publisher, 2022)
This study aims to analyze the Effect of the Human Resources Audit and Internal Control System on Employee Performance at PT. Subur Sedaya Maju In Prabumulih